2013
DOI: 10.1017/s1479262112000512
|View full text |Cite
|
Sign up to set email alerts
|

Seed oil content and fatty acid composition in a genebank collection of Cucurbita moschata Duchesne and C. argyrosperma C. Huber

Abstract: Data on intra-specific variability for seed oil content, physical characteristics and fatty acid composition in Cucurbita moschata and Cucurbita argyrosperma are lacking in the scientific literature. We examined 528 genebank accessions of C. moschata and 166 accessions of C. argyrosperma -which included members of both subsp. argyrosperma and subsp. sororia -for seed oil content, oil physical characteristics and fatty acid composition. The oil of both species had near-identical viscosities, viscosity indices, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…Also it was reported that oleic and palmitic acid contents of pepper seeds showed similar values, oleic acid content changed between 6.4% and 13.6% in fresh and between 9.3% and 10.7% in dried seeds. Plus, Jarret et al (2013) indicated that the most abundant fatty acid of the tested Capsicum species was linoleic acid (73.92-77.93%), followed by palmitic (10.62-14.43%), oleic (5.42-7.58%) and stearic (2.74-3.95%) acids. Results of this work were similar and agreed with the above mentioned studies.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Also it was reported that oleic and palmitic acid contents of pepper seeds showed similar values, oleic acid content changed between 6.4% and 13.6% in fresh and between 9.3% and 10.7% in dried seeds. Plus, Jarret et al (2013) indicated that the most abundant fatty acid of the tested Capsicum species was linoleic acid (73.92-77.93%), followed by palmitic (10.62-14.43%), oleic (5.42-7.58%) and stearic (2.74-3.95%) acids. Results of this work were similar and agreed with the above mentioned studies.…”
Section: Resultsmentioning
confidence: 97%
“…Although a number of papers exist regarding the characterization of the seeds oils and fatty acid composition of different vegetable crops' seeds (Barthet, 2008;Mortley et al, 2012;Jarret et al, 2013), most do not cover the relations between fatty acid composition and seed germination and vigour under stressful temperatures. Therefore, the present study was undertaken to determine the fatty acid profile of seeds of pepper (Capsicum annuum L.) cultivars, as well as the relations between fatty acid profile, seed germination and vigour under controlled conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The crop also has potential for the production of edible seed oil. Its seed oil comprises about 70% unsaturated fatty acids, and it has a high content of monounsaturated fatty acids [10,11,12], so it is a good substitute for other lipid sources that have higher contents of saturated fatty acids. The oil is also rich in bioactive components such as vitamin E and carotenoids [13], which are important antioxidants in the human diet, in addition to protecting the oil itself against oxidative processes.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of C. moschata for the production of edible seed oil is also a promising aspect of this crop. Constituted of about 70% unsaturated fatty acids with a high content of monounsaturated fatty acid [12, 13], C. moschata seed oil is a good substitute for other lipid sources with higher saturated fatty acid contents. The oil is also rich in bioactive components such as vitamin E and carotenoids [4], which are important antioxidants in the human diet, in addition to providing protection to the oil against oxidative processes.…”
Section: Introductionmentioning
confidence: 99%